Combined effects of straw-derived biochar and bio-based polymer-coated urea on nitrogen use efficiency and cotton yield. Issue 1 (1st January 2018) - Yu, Xiaojing; Tian, Xiaofei; Lu, Yanyan; Liu, Zhiguang; Guo, Yanle; Chen, Jianqiu; Li, Chengliang; Zhang, Min; Wan, Yongshan
ABSTRACT: The interactive effects of straw-derived biochar and bio-based polymer-coated urea (BPCU) was examined with a pot experiment conducted in 2014 and 2015. Using a split-plot design, the main plot factor was the form of straw use and the sub-plot factor was the type of N fertilizer. The soil inorganic nitrogen (N), organic carbon and lint yield of biochar treatments were significantly higher than for straw treatments. Meanwhile, the BPCU treatments enhanced nitrogen use efficiency (NUE) and yield over urea treatments. Biochar combined with BPCU resulted in the highest lint yield, 14.3–108.2% increasing over the other treatments, with NUE 27.1–63.5% increased. We attributed this superior performance to the interactive effects between BPCU's controlled supply of N according to cotton's N requirements and biochar's functionalities in enhancing soil quality. Thus, the application of biochar and BPCU is a sustainable strategy to improve soil quality and increase cotton yield.